Decay and renormalization of a longitudinal mode in a quasi-two-dimensional antiferromagnet - Seung-Hwan Do (Nature Portfolio, 2021)
Anisotropic spin S >1/2 quantum magnets can have multiple low energy modes. In this manuscript, the authors study the interaction of such low energy modes in the S = 1 antiferromagnet Ba2FeSi2O7 by combining neutron scattering measurements with an SU(3) generalization of the 1/S expansion.